A theory of aggregate consumption - KIM, Yun K. (Institutional Knowledge at Singapore Management University, 2014)
We develop a Keynesian model of aggregate consumption. Our theory emphasizes the importance of the relative income hypothesis and debt finance for understanding household consumption behavior. It is shown that particular importance attaches to how net debtor households service their debts, and that the treatment of debt-servicing commitments as a substitute for savings by these households creates the potential for 'sudden stops' in consumption spending (and hence aggregate demand).